AUTHORITY OF TEACHER OF TECHNICAL AND COMPUTER SCIENCE BASED ON STUDENTS OPINION - Noga, Henryk; Nesterak, Tomasz; Katarzyna Grzegorzewska, Maria (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Teacher profession has entails a huge responsibility. At work of a teacher, his character traits are key. Today, in the era of mass media, when in every home we can find a computer connected to the Internet, it is difficult to teacher to have the authority in students eyes. The main objective of this study is to learn about the level the teacher's authority of technical subjects - information technology.